2013
DOI: 10.1111/ipd.12062
|View full text |Cite
|
Sign up to set email alerts
|

Hospital admissions for dental treatment among children with cleft lip and/or palate born between 1997 and 2003: an analysis of Hospital Episode Statistics in England

Abstract: Factors increasing the risk of hospital admission among cleft children should be taken into account when planning services. Efforts to reduce the number of hospital admissions should be focused on disease prevention, particularly among those most at risk of caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Our results demonstrate that both cleft type and school absence are independently associated with academic attainment in children with a cleft.InterpretationDifferences in annual school absence levels between 7-year-old children with an isolated orofacial cleft and corresponding children in the general population are due to differences in length of absence for illness and medical/dental appointments. This is in line with our previously published observations that children with more complex cleft types require more interventions from multiple specialties, including grommets insertions and dental procedures requiring general anaesthetic [3,7].…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Our results demonstrate that both cleft type and school absence are independently associated with academic attainment in children with a cleft.InterpretationDifferences in annual school absence levels between 7-year-old children with an isolated orofacial cleft and corresponding children in the general population are due to differences in length of absence for illness and medical/dental appointments. This is in line with our previously published observations that children with more complex cleft types require more interventions from multiple specialties, including grommets insertions and dental procedures requiring general anaesthetic [3,7].…”
supporting
confidence: 92%
“…. [1] A cleft can affect hearing, [2,3] language, [4,5] dental health, [6,7] psychosocial health, [8] neurodevelopmental health, [9] and academic outcomes. [9,10] Recently, we have shown that the presence of an isolated cleft (a cleft without additional anomalies or syndromes) negatively affects all areas of learning, especially when the cleft involves the palate (both CPO and CLP).…”
mentioning
confidence: 99%
“…The consequences of caries may be to increase the burden of care through additional treatment visits and increased risk of pain and risk of sepsis. Children with cleft lip and palate are more likely to have a general anaesthetic for dental treatment before the age of seven years than their peers , and this adds further to their number of hospital admissions.…”
Section: Introductionmentioning
confidence: 99%
“…52 The remaining 18 studies identified CMs from secondary care data, with most assessing health service delivery, surgical outcomes or disease trends. [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] Almost all used HES (n = 16) and the most commonly identified CMs were heart (n = 4) and orofacial defects (n = 4).…”
Section: Resultsmentioning
confidence: 99%